The Effect of Digital Marketing and Brand Awareness on Purchase Decisions through Engagement with Promotion as Moderator - Abdul Hakim; Ayuningtyas Putri Mumpuni Halim Asy’ary; Asraf Asraf; Laode Hamida (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study is motivated by the rapid growth of e-commerce in Indonesia, where digital interactions increasingly shape consumer purchasing decisions, while prior findings regarding digital marketing, brand awareness, customer engagement, and promotion remain partially contradictory. The purpose of this study is to examine the effects of digital marketing and brand awareness on customer engagement and purchase decisions, as well as to test the mediating role of customer engagement and the moderating role of promotion. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with 234 respondents selected through purposive sampling. The results indicate that digital marketing and brand awareness have significant positive effects on both customer engagement and purchase decisions. Customer engagement is identified as the most dominant variable and partially mediates these relationships. In contrast, promotion shows no significant direct effect on purchase decisions and does not moderate the relationship between customer engagement and purchase decisions. The findings imply that e-commerce strategies should prioritize engagement-driven approaches and brand strengthening rather than relying heavily on promotional incentives. In conclusion, purchase decisions in digital marketplaces are more strongly driven by customer engagement and brand-related factors than by promotional stimuli.